Application of polyethylene glycol, cetrimide, chitosan and their mixtures on cotton muslin fabric to improve rot resistance, antimicrobial property and its salt-free reactive dyeing. Issue 11 (1st November 2016) - Samanta, Ashis Kumar; Mukhopadhyay, Asis; Bhagwat, Madhusudan M.; Kar, Tapas Ranjan
Abstract : In the present work, cotton muslin fabric is treated with eco-friendly antimicrobial agents in order to observe the effect of those chemicals on the rot resistance properties, physical appearance, important textile-related mechanical properties and dyeability with reactive dyes. The cotton fabric has been treated with polyethylene glycol (PEG 200), cetrimide and chitosan individually and their blends, in the presence of citric acid and sodium hydrogen phosphate as mixed catalyst to investigate the effect of such treatment on fabric properties of treated cotton mentioned above. Amongst all individual and combined applications of above said chemicals, it is observed that treatment with a mixture of chitosan and PEG is showing good result in terms of improvement in rot resistance performance and an optimum balance in other textile-related mechanical and appearance properties indicating lowest degradation against microbial attack. A series of experiments were undertaken with varying percentage of both the chemicals to arrive at the optimum ratio of mixture of PEG and chitosan and compared with such effect for treatment with conventional quaternary ammonium compound EPTAC. This treatment shows much balance results and also creates a newer provision of salt-free reactive dyeing of such treated/cationized cotton muslin fabric by unconventional reactive dyeing in acid bath after such chemical treatment/modifications.